2021
DOI: 10.1021/acs.jpcc.1c00339
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Incorporation of Zirconium into BiVO4 Visible-Light Photocatalyst

Abstract: Monoclinic BiVO4 is a promising material for realizing low-cost visible-light water splitting. Here, we report the incorporation mechanism of Zr into solution-processed BiVO4. Characterization of the crystal structure confirmed the incorporation of Zr into the BiVO4 lattice and the formation of single-phase monoclinic crystals at lower Zr concentrations. Characterization of the electronic stucture suggested that Zr acts as a shallow donor indicated that Zr acts as a shallow donor. The Zr-doped sample showed h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…An emission peak at 512 nm for both BiVO 4 and Bi 1−x VO 4 can be ascribed to the band−band PL phenomenon that is similar to the band-gap energy of 517 nm, while another emission peak of an intra-band state at 668 and 713 nm, respectively for BiVO 4 and Bi 1−x VO 4 can be associated with the surface recombination of electron/hole. [18,40] Compared to pristine BiVO 4 , the emission peaks of Bi 1−x VO 4 from both band-band recombination and inter-band recombination are dramatically increased, and the emission peak from inter-band recombination significantly shifted to 713 nm. The phenomenon might be due to the suppressed charge recombination at the bulk self-trapped state of Bi 1−x VO 4 , which in turn leads to more freely moving carriers to recombine at the intra-band state (surface carrier trappers).…”
Section: Resultsmentioning
confidence: 99%
“…An emission peak at 512 nm for both BiVO 4 and Bi 1−x VO 4 can be ascribed to the band−band PL phenomenon that is similar to the band-gap energy of 517 nm, while another emission peak of an intra-band state at 668 and 713 nm, respectively for BiVO 4 and Bi 1−x VO 4 can be associated with the surface recombination of electron/hole. [18,40] Compared to pristine BiVO 4 , the emission peaks of Bi 1−x VO 4 from both band-band recombination and inter-band recombination are dramatically increased, and the emission peak from inter-band recombination significantly shifted to 713 nm. The phenomenon might be due to the suppressed charge recombination at the bulk self-trapped state of Bi 1−x VO 4 , which in turn leads to more freely moving carriers to recombine at the intra-band state (surface carrier trappers).…”
Section: Resultsmentioning
confidence: 99%
“…As we know, BiVO 4 with low carrier mobility is unfavorable in regards to photocatalytic activity. Therefore, extensive efforts have been conducted to improve photocatalytic performance, such as loading noble metal, control morphology, exposed specific facets, , doping, , decorating oxide, defect engineering, , and constructing heterojunctions with other semiconductors. Generally, doping has been proved to be an effective method to improve carrier mobility in the bulk and surface of BiVO 4 . For example, BiVO 4 doped with several metals, such as Cu, Eu, Tb, and Mo, can greatly improve the carrier mobility and thus improve the photocatalytic activity of BiVO 4 .…”
Section: Introductionmentioning
confidence: 99%
“…15−18 Nevertheless, the practical photocatalytic efficiency of pure BiVO 4 is much lower than what is expected owing to relatively unsatisfactory visible-light utilization and low electron transfer rate. 1,19 Previous reports have confirmed that approximately 60−80% of the photogenerated carriers recombined before reaching the interfaces, which significantly reduced the photocatalytic activity of BiVO 4 . 15,20,21 Moreover, the susceptibility of BiVO 4 to photocorrosion limits the long-term stability that is necessary for practical applications.…”
Section: Introductionmentioning
confidence: 98%
“…Recently, the monoclinic bismuth vanadate (BiVO 4 ) has been extensively studied in the fast-moving fields of visible-light photocatalysis due to its facile synthesis, strong oxidation ability, and structural stability. Nevertheless, the practical photocatalytic efficiency of pure BiVO 4 is much lower than what is expected owing to relatively unsatisfactory visible-light utilization and low electron transfer rate. , Previous reports have confirmed that approximately 60–80% of the photogenerated carriers recombined before reaching the interfaces, which significantly reduced the photocatalytic activity of BiVO 4 . ,, Moreover, the susceptibility of BiVO 4 to photocorrosion limits the long-term stability that is necessary for practical applications . Nevertheless, photocorrosion can be dynamically suppressed when the interfacial charge transfer rate is higher than the photocorrosion rate .…”
Section: Introductionmentioning
confidence: 99%